APPLYING ROLE PLAY TECHNIQUE TO IMPROVE SPEAKING ABILITY OF ELEVENTH-GRADE STUDENTS’ AT SMA NEGERI 1 KAYAN HULU - Yokie; Ilinawati (Lingustic, Literature and English Education, 2025)
This study investigates the effectiveness of role-play techniques in enhancing speaking skills and increasing student participation among eleventh graders at SMA Negeri 1 Kayan Hulu. The research was motivated by initial observations that students were reluctant to participate and lacked confidence in speaking activities. Role play was selected as the primary strategy because it offers students opportunities to practice real-life communication in a supportive and engaging environment. Employing a classroom action research design, data were collected through observations, interviews, field notes, and documentation. The findings confirmed the hypothesis that role play would improve both participation and speaking performance. Participation scores rose from 69 in the first cycle to 81 in the second, while speaking performance improved from 54 to 80. The study concludes that role play is an effective method for developing students’ speaking abilities and encouraging greater classroom participation. It is recommended that teachers implement role play regularly using varied scenarios, engage in professional development, conduct periodic evaluations, and involve students in scenario creation to maximize the method’s effectiveness.